EFFECTIVE WAYS OF TEACHING PAST TENSES IN THE ENGLISH LANGUAGE - Gafurjanova Ferangiz (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This article examines effective methods of teaching past tenses in English, focusing on both theoretical and practical aspects of grammar instruction. It analyzes common learner difficulties, including confusion between tense and aspect, and highlights strategies such as explicit explanation, inductive learning, storytelling, role- plays, and task-based activities. The importance of corrective feedback and the integration of digital tools are also discussed. The study concludes that a balanced approach combining accuracy and communicative practice is essential for successful mastery of past tense forms.